Approximation of Generalized Left Derivations - Sheon-Young Kang; Ick-Soon Chang (Abstract and Applied Analysis)
We need to take account of the superstability for generalized left derivations (resp., generalized derivations) associated with a Jensen-type functional equation, and we also deal with problems for the Jacobson radical ranges of left derivations (resp., derivations).